Helicobacter pylori Infection in Pediatric Patients Living in Europe: Results of the EuroPedHP Registry 2013 to 2016. Issue 4 (October 2020) - Kori, Michal; Le Thi, Thu Giang; Werkstetter, Katharina; Sustmann, Andrea; Bontems, Patrick; Lopes, Ana Isabel; Oleastro, Monica; Iwanczak, Barbara; Kalach, Nicolas; Misak, Zrinjka; Cabral, José; Homan, Matjaž; et al.
ABSTRACT: Objectives: The aim of the study was to assess clinical presentation, endoscopic findings, antibiotic susceptibility and treatment success of Helicobacter pylori ( H. pylori ) infected pediatric patients. Methods: Between 2013 and 2016, 23 pediatric hospitals from 17 countries prospectively submitted data on consecutive H. pylori -infected (culture positive) patients to the EuroPed HP- Registry. Results: Of 1333 patients recruited (55.1% girls, median age 12.6 years), 1168 (87.6%) were therapy naïve (group A) and 165 (12.4%) had failed treatment (group B). Patients resided in North/Western (29.6%), Southern (34.1%) and Eastern Europe (23.0%), or Israel/Turkey (13.4%). Main indications for endoscopy were abdominal pain or dyspepsia (81.2%, 1078/1328). Antral nodularity was reported in 77.8% (1031/1326) of patients, gastric or duodenal ulcers and erosions in 5.1% and 12.8%, respectively. Primary resistance to clarithromycin (CLA) and metronidazole (MET) occurred in 25% and 21%, respectively, and increased after failed therapy. Bacterial strains were fully susceptible in 60.5% of group A, but in only 27.4% of group B. Primary CLA resistance was higher in Southern and Eastern Europe (adjusted odds ratio [ORadj ] = 3.44, 95% confidence interval [CI] 2.22–5.32, P  < 0.001 and 2.62, 95% CI: 1.63–4.22, P  < 0.001, respectively) compared with Northern/Western Europe. Children born outside Europe showed higher primary MET resistance (ORadj  = 3.81, 95% CI: 2.25–6.45, P  < 0.001). Treatment success in group A reached only 79.8% (568/712) with 7 to 14 days triple therapy tailored to antibiotic susceptibility. Conclusions: Peptic ulcers are rare in dyspeptic H. pylori -infected children. Primary resistance to CLA and MET is markedly dependent on geographical regions of birth and residence. The ongoing survey will show whether implementation of the updated ESPGHAN/NASPGHAN guidelines will improve the eradication success. Abstract : Supplemental Digital Content is available in the text